2001
DOI: 10.1111/j.1469-8749.2001.tb00746.x
|View full text |Cite
|
Sign up to set email alerts
|

Angelman syndrome: evolution of the phenotype in adolescents and adults

Abstract: Individuals with Angelman syndrome (AS) have severe learning disability, * at axia, seizures, dysmorphic facies, a happy, sociable disposition, and inability to speak. Most of the literature concerning the clinical features of AS has concentrated on younger children. This study aimed to look at the natural history of AS by documenting the clinical features in a group of 28 adolescents and adults with AS (12 males, 16 females; age range 16 to 40 years). Specific aspects studied included physical characteristics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
60
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(66 citation statements)
references
References 19 publications
4
60
2
Order By: Relevance
“…In examining these changes in ABC‐C scores with age, while rates of lethargy and stereotypy remained low over time, all participants experienced an increase in irritability and hyperactivity with advancing age. This increase in hyperactivity with age in our study is not consistent with other studies, which had found that adults had lower hyperactivity scores than adolescents (Clarke & Marston, ; Clayton‐Smith, ). However, given the relatively young ages of the participants in our cohort, our findings should be interpreted with caution for adults.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In examining these changes in ABC‐C scores with age, while rates of lethargy and stereotypy remained low over time, all participants experienced an increase in irritability and hyperactivity with advancing age. This increase in hyperactivity with age in our study is not consistent with other studies, which had found that adults had lower hyperactivity scores than adolescents (Clarke & Marston, ; Clayton‐Smith, ). However, given the relatively young ages of the participants in our cohort, our findings should be interpreted with caution for adults.…”
Section: Discussioncontrasting
confidence: 99%
“…Research on the changes in problem behaviors with age in individuals with developmental disabilities has been inconsistent, with some studies noting stability of these behaviors in childhood (Matson, Mahan, Hess, Fodstad, & Neal, ), while others noting a decrease in irritability and hyperactivity over time (Brown, Aman, & Havercamp, ). A study in the AS population noted a decrease in hyperactivity in adolescence and adulthood (Clayton‐Smith, ), while another study examing AS adolescents and adults noted an increase in anxiety in adults and a decrease in defiant behaviors (Prasad, Grocott, Parkin, Larson &Thibert, ). However, to date, no published studies have examined changes in a variety of maladaptive behaviors in AS over time.…”
Section: Introductionmentioning
confidence: 99%
“…We observed that the AS symptoms change with age, reflecting the maturational pattern of the brain, as previously observed in AS adults [3,28]. It is important for clinicians to understand the clinical and EEG features of adult AS.…”
Section: Discussionmentioning
confidence: 48%
“…We identified only one patient with pUPD with clinical features more moderate in comparison to patients with deletion. He did not have seizures and his speech was better like it was published in similar case by (Smith, 2001). Mutations within the UBE3A gene give rise to a typical but more severe clinical presentation Science Publications OJBS without hypopigmentation.…”
Section: Discusionmentioning
confidence: 74%